Perancangan Alat Pemotongan Rumput Menggunakan Tenaga Surya (Solar Cell) 20 WP: pemotong rumput menggunakan tenaga surya - Tampubolon, Mora Tama; Roza, Indra; Ananda, Yussa (Universitas Harapan Medan, 2024)
Solar cells are the conversion of solar energy into electrical energy which can be used in various tools such as lawn mowers in fields and parks. The use of lawn mowers so far still uses energy that is used up or cannot be renewed, for example petroleum or other fuels. And what is often found among the public still uses fuel oil (BBM). Based on these things, a grass cutting machine was designed whose current source was taken from sunlight as a power source to run the DC motor on the grass cutter, so as to reduce air pollution or the sound generated by the machine to create environmentally friendly. Electricity from an electric lawn mower sourced from the sun is absorbed directly by the 20WP solar cell, which will flow to the solar charge controller to control the charging of the 12V battery. not available, from the battery the current flows to the potentiometer which functions to regulate the speed of the cutting blade on the lawn mower, after going through the potentiometer the current flows to the switch which functions to turn off and start the lawn mower, after passing through the switch the current flows to the 12V DC motor which functions to move the lawn mower blade . Electric lawn mowers are very suitable for people who prioritize environmental cleanliness and comfort, because this lawn mower is very environmentally friendly and quieter to use.